Simulação dos impactos da urbanização sobre as inundações urbanas na bacia hidrográfica do rio Cuiá (PB) - Costa, Antônio Henrique Araújo (2013)
The intense population growth of the last decades has shown the lack of urban planning of brazilian cities. The disordered urbanization process involves directly in increased impervious areas, changing natural conditions and interfering in hydrological cycle. The metropolitan area of the João Pessoa city, Paraíba, has suffered from urban expansion without urban planning and has seen various impacts, such as floods. In the region of the river Cuiá basin, located in southern coastline of Paraíba, in the municipality of João Pessoa, between the UTM coordinates 9.210.000N/302.000E e 9200.00N/292.000E, such events have been repeated in periods of heavier rainfall. In this sense, the application of hydrological models has been recommended for prediction of impacts on water resources and assists in the decision making of managers. Thus, this study aims to estimate the impacts of urbanization on flooding in the river Cuiá basin. For this, we used the hydrological models IPH II and HEC-RAS and considered three urbanization scenarios (current, trend and critic), defined based on certain percentages of soil sealing and urban occupation. The rainfall-runoff simulations were performed considering rainfall with return period of 10, 50 and 100 years allowed us to estimate the impacts on the flows generated, on peak times and on floodplains of the basin. With the simulation results, it was found that the lower frequency rainfall results in peak flow up to 80% higher than the highest frequency. Under the same conditions, peak times were reduced on average by 10% when compared to the critical and current scenarios. The flood simulations generated information that allowed create the flood maps. Considering the potencial of flood scenarios more critical and less frequent events, floodplains can be as much as 13% higher than in the current scenario.